The Right to Strike for State and Private Sector Employees in Iraqi Legislation : A comparative study - Salem , Mustafa (Journal of Legal Sciences, 2023)
The majority of constitutions stipulate and regulate public rights and freedoms in them, including the right to strike as one of the means of expressing an opinion, which public officials or workers resort to in the labor law in order to improve their working conditions and achieve legitimate professional demands while continuing the work of the public facility, However, his capacity as a public servant imposes some restrictions on him in his exercise of political freedoms, including the right to strike because it intersects with the principle of the continuation of the regular and steady functioning of public utilities, which governs the work of public utilities in satisfying the public needs of individuals. The Iraqi legislator permitted private-sector workers without state and public sector employees, although the legislator considered it a means of expressing an opinion. We divided our research into three sections. The first is entitled the nature of the strike, the second is entitled to the legal nature of the strike, its forms, and its legitimacy, and the third is entitled to the controls and restrictions on exercising the right to strike and its consequences. We concluded that the strike is not an absolute right from every restriction, but rather is subject to controls and restrictions that ensure that it is exercised in accordance with the public order, and the recommendation to quickly legislate the strike law for state employees and the public sector, like the private sector